2021
DOI: 10.1161/hypertensionaha.121.17567
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Maternal sFLT1 (Soluble fms-Like Tyrosine Kinase-1) Is Sufficient to Impair Spiral Arterial Remodeling in a Preeclampsia Mouse Model

Abstract: One driving factor for developing preeclampsia—a pregnancy disorder, often associated with poor spiral artery (SpA)-remodeling and fetal growth restriction—is the anti-angiogenic sFLT1 (soluble fms-like tyrosine kinase-1), which is found to be highly upregulated in preeclampsia patients. The sFLT1-mediated endothelial dysfunction is a common theory for the manifestation of maternal preeclampsia symptoms. However, the influence of sFLT1 on SpA-remodeling and the link between placental and maternal preeclampsia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 56 publications
4
54
0
Order By: Relevance
“…Our own previous work using an experimental transgenic human sFLT1- (hsFLT1-) related PE/FGR mouse model clearly showed that elevated hsFLT1 levels in maternal circulation resulted in placental dysfunction characterized by increased placental hypoxia, shown by an increase in hypoxia-inducible factors ( Hif1α , Hif2α ), leading to foetal growth restriction already starting at the end of the second trimester during pregnancy with viable and nonviable foetuses. Our previous results supported the hypothesis that this was due to reduced uteroplacental vascularization including impaired spiral arterial remodelling and foetal vessel development in the placental labyrinth [ 11 , 12 ].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our own previous work using an experimental transgenic human sFLT1- (hsFLT1-) related PE/FGR mouse model clearly showed that elevated hsFLT1 levels in maternal circulation resulted in placental dysfunction characterized by increased placental hypoxia, shown by an increase in hypoxia-inducible factors ( Hif1α , Hif2α ), leading to foetal growth restriction already starting at the end of the second trimester during pregnancy with viable and nonviable foetuses. Our previous results supported the hypothesis that this was due to reduced uteroplacental vascularization including impaired spiral arterial remodelling and foetal vessel development in the placental labyrinth [ 11 , 12 ].…”
Section: Introductionsupporting
confidence: 88%
“…Taking into account that human sFLT1 (hsFLT1) overexpression revealed a negative impact on fetoplacental [ 11 ] and uteroplacental vascularization [ 12 ] as well as foetal body weight gain during pregnancy [ 11 , 12 ] in our hsFLT1-transgenic PE mouse model, we conjectured that systemic hsFLT1 overexpression impairs foetal neurodevelopment during pregnancy due to undernutrition and underperfusion of the placenta and foetus and thereby might promote long-lasting neurodevelopmental deficits in PE offspring independent of prematurity.…”
Section: Introductionmentioning
confidence: 99%
“…Since numerous prior studies have shown that higher serum levels of sFlt-1 and sEng contribute to the pathogenesis of PE 19, 20, 22, 23 , we measured the concentration of these anti-angiogenic factors using respective ELISA kits. The analysis showed significantly higher levels of sFlt-1 and sEng in the sera from pregnant huTTR mice when compared with age-matched pregnant wild-type mice (Figure 5E and F).…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic or adenoviral overexpression of sFLT1 alone or in combination with sENG develops more robust preeclampsia phenotypes, including severe hypertension, nephrotic range proteinuria, cerebral edema, and HELLP like phenotypes. [41][42][43]95 Taken together with the data that, in humans, high levels of sFLT1 and sENG correlate with adverse maternal and fetal outcomes, 20 there has been great interest in testing targeted therapies for preeclampsia in antiangiogenic overexpression model. A significant limitation of the rodent model, however, is lack of expression of all the isoforms of sFLT1 expressed in humans, 96 making it difficult to study molecular therapies such as antibodies that preferentially bind one isoform over others.…”
Section: Summary Of Preeclampsia Modelsmentioning
confidence: 99%